PERSEPSI MAHASISWA MENGENAI DAMPAK PENERAPAN METODE PEMBELAJARAN DOSEN (Studi Pada Jurusan Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar) - Hafid, Erwin; ., Bahraeni; ., Usman (Inspiratif Pendidikan, 2018)
Abstract: This paper is the result of research that is motivated by the importance of majors at universities to know the quality of lecturers learning after the learning activities take place by looking at the perception of students. This study describes the impact of the impact of the application of lecturer teaching methods at the Department of Islamic Education Faculty of Tarbiyah and UGM Teachers Alauddin Makassar. This research is located at UIN Alauddin Makassar with research population all students of Department of Islamic Education Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. The result of the research shows that the impact of the application of lecturer’s teaching method at the Department of Islamic Education Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar can be seen through several forms: (a) easy to reach the learning goal 65.26% agreeing (Good category); (b) easy to understand learning materials 75.79% agreed (Good category); (c) effectively achieve learning objectives 80% agree (excellent category); (d) increase student learning motivation 77.89% agreed (good category); (e) increase student interest 80% agree (good category); (f) create an active learning atmosphere 83.16% agree (excellent category); (g) create an interesting learning atmosphere of 75.79% (Good category); (h) create a fun learning atmosphere 80% agree (Good category); (i) establishing students’ familiarity 74.74% agreeing (Good category); (j) build positive communication between students and lecturers 81.05% agreed (very good category); (k) build a religious attitude 80% students agree (good category); (l) to form social attitudes 89.47% students agree (very good category); (m) form emotional attitudes of students 69.47% agreed (Good category).